A review on biomass as a fuel for boilers - Saidur, Rahman; Abdelaziz, E.A.; Demirbas, A.; Hossain, M.S.; Mekhilef, Saad (Elsevier, 2011)
Currently, fossil fuels such as oil, coal and natural gas represent the prime energy sources in the world. However, it is anticipated that these sources of energy will deplete within the next 40-50 years. Moreover, the expected environmental damages such as the global warming, acid rain and urban smog due to the production of emissions from these sources have tempted the world to try to reduce carbon emissions by 80 and shift towards utilizing a variety of renewable energy resources (RES) which are less environmentally harmful such as solar, wind, biomass etc. in a sustainable way. Biomass is one of the earliest sources of energy with very specific properties. In this review, several aspects which are associated with burning biomass in boilers have been investigated such as composition of biomass, estimating the higher heating value of biomass, comparison between biomass and other fuels, combustion of biomass, co-firing of biomass and coal, impacts of biomass, economic and social analysis of biomass, transportation of biomass, densification of biomass, problems of biomass and future of biomass. It has been found that utilizing biomass in boilers offers many economical, social and environmental benefits such as financial net saving, conservation of fossil fuel resources, job opportunities creation and CO 2 and NO x emissions reduction. However, care should be taken to other environmental impacts of biomass such as land and water resources, soil erosion, loss of biodiversity and deforestation. Fouling, marketing, low heating value, storage and collections and handling are all associated problems when burning biomass in boilers. The future of biomass in boilers depends upon the development of the markets for fossil fuels and on policy decisions regarding the biomass market.